Why do architects wear black? - Rau, Cordula (Birkhäuser, 2017)
"Why is it really that architects wear black? was a question put to Cordula Rau by an automotive industry manager during an architectural competition. Even though she herself is an architect, and wears black, she did not have an answer on the spot. So she decided to ask other architects, as well as artists and designers. She has been collecting their handwritten replies in a notebook since 2001"--Publisher's website